MX2: a high‐flux undulator microfocus beamline serving both the chemical and macromolecular crystallography communities at the Australian Synchrotron. (6th April 2018) - Aragão, David; Aishima, Jun; Cherukuvada, Hima; Clarken, Robert; Clift, Mark; Cowieson, Nathan Philip; Ericsson, Daniel Jesper; Gee, Christine L.; Macedo, Sofia; Mudie, Nathan; Panjikar, Santosh; Price, Jason Roy; et al.
Abstract : A microfocus macromolecular crystallography beamline at the Australian Synchrotron is presented. Abstract : MX2 is an in‐vacuum undulator‐based crystallography beamline at the 3 GeV Australian Synchrotron. The beamline delivers hard X‐rays in the energy range 4.8–21 keV to a focal spot of 22 × 12 µm FWHM (H × V). At 13 keV the flux at the sample is 3.4 × 10 12 photons s −1 . The beamline endstation allows robotic handling of cryogenic samples via an updated SSRL SAM robot. This beamline is ideal for weakly diffracting hard‐to‐crystallize proteins, virus particles, protein assemblies and nucleic acids as well as smaller molecules such as inorganic catalysts and organic drug molecules. The beamline is now mature and has enjoyed a full user program for the last nine years. This paper describes the beamline status, plans for its future and some recent scientific highlights.